Steel plate and its manufacturing method
By adjusting the hot rolling conditions and maintaining the inhomogeneity of the steel plate surface, the problem of insufficient energy absorption performance of high-strength steel plates in the prior art during impact impact is solved, and the dual effects of high energy absorption and surface inhomogeneity in the manufacturing process are achieved.
Patent Information
- Application Number
- JP2023510583
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-04-02
- Filing Date
- 2022-02-07
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2042-02-07
AI Technical Summary
The prior art is difficult to effectively improve the energy absorption performance of high-strength steel plates during impact impact, and it is difficult to maintain the inhomogeneity of the steel plate surface during the manufacturing process to improve the energy absorption effect.
By adjusting the hot rolling conditions, the inhomogeneity of the steel plate surface is increased and the incompletely smooth baking treatment is performed after hot rolling, ensuring that the steel plate maintains surface unevenness during cold rolling and annealing, thereby improving the energy absorption performance of the steel plate during impact impact.
The high energy absorption performance of the steel plate during impact impact is achieved, and the ideal inhomogeneity of the steel plate surface is maintained during the manufacturing process, improving the overall performance of the steel plate.
Smart Images

Figure 0007662962000011 
Figure 0007662962000012 
Figure 0007662962000001
Abstract
Description
[Technical field]
[0001] The present application discloses a steel sheet and a method for manufacturing the same. [Background technology]
[0002] In recent years, efforts to reduce the weight of automobile bodies have been made by applying high-strength steel sheets in order to improve the fuel efficiency of automobiles. Also, to ensure the safety of passengers, high-strength steel sheets are increasingly being used in automobile bodies instead of mild steel sheets. In order to further reduce the weight of automobile bodies in the future, the strength level of high-strength steel sheets must be increased more than ever before.
[0003] Furthermore, automobile parts are required to deform during an automobile collision and exhibit high energy absorption. In order to increase the energy absorbed by the deformation of automobile parts during an automobile collision, it is desirable to prevent the fracture of steel that occurs during crush deformation of the automobile parts. For this reason, steel plates used in automobile parts are required to have high strength and exhibit excellent energy absorption during crush deformation. However, in the prior art, although the workability and the like of high-strength steel plates have been studied (for example, Patent Documents 1 to 3 below), sufficient study has not been made on the energy absorption during crush deformation.
[0004] Patent Document 1 discloses a method for inexpensively producing a high-carbon cold-rolled steel strip that is softened and has excellent workability while preventing the occurrence of seizing defects, by cold rolling a hot-rolled steel strip containing 0.3-1.3% C, 0.03-0.35% Si, and 0.20-1.50% Mn, with the balance being essentially Fe and unavoidable impurities, at a rolling reduction of 20% to 85%, and then annealing the strip in a bell-type batch annealing furnace in a gas atmosphere containing 75% or more by volume of hydrogen and the balance being essentially nitrogen and unavoidable impurities, at a heating rate of 20-100°C / Hr to Ac1 point to Ac1 point + 50°C, holding the steel soaked for 8 hours or less, and then cooling to Ar1 point or less at a cooling rate of 50°C / Hr or less.
[0005] Patent Document 2 discloses a steel sheet for processing having excellent paint clarity, characterized in that the surface of the steel sheet is formed into an uneven rough surface, the wavelength λ of the uneven pattern on the rough surface is set to 500 μm or less, and the center line average roughness Ra is set to the range of 1 to 5 μm.
[0006] Patent Document 3 discloses a steel sheet having a predetermined chemical composition, and a metal structure containing, by area ratio, 40.0% or more and less than 60.0% polygonal ferrite, 30.0% or more bainitic ferrite, 10.0% or more and 25.0% or less retained austenite, and 15.0% or less martensite, wherein the retained austenite has an aspect ratio of 2.0 or less, a major axis length of 1.0 μm or less and a minor axis length of 1.0 μm or less, and a proportion of the retained austenite is 80.0% or more, the bainitic ferrite has an aspect ratio of 1.7 or less and a proportion of 80.0% or more bainitic ferrite having an average crystal orientation misorientation of 0.5° or more and less than 3.0° in regions surrounded by grain boundaries having a crystal orientation misorientation of 15° or more, and a connectivity D value between the martensite, the bainitic ferrite, and the retained austenite is 0.70 or less. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 10-204540 [Patent Document 2] Japanese Patent Application Publication No. 4-253503 [Patent Document 3] Patent No. 6791838 Summary of the Invention [Problem to be solved by the invention]
[0008] In view of the above circumstances, the present application discloses a steel sheet having excellent energy absorbency during crushing deformation, and a method for manufacturing the same. [Means for solving the problem]
[0009] The inventors have intensively studied methods for solving the above problems and have clarified that a steel sheet exhibiting excellent energy absorption during crushing deformation can be obtained by increasing the surface unevenness of the steel sheet and introducing deformation starting points on the steel sheet surface. In addition, they have confirmed that in a steel sheet with a smooth surface, deformation is localized during crushing, resulting in an accidental decrease in absorbed energy.
[0010] The present inventors have also found that the above-mentioned steel sheet can be manufactured by an integrated manufacturing method characterized by increasing the surface irregularities of the hot-rolled sheet by adjusting the hot-rolling conditions, and then carrying out an annealing process without completely smoothing out the irregularities.
[0011] Furthermore, the inventors have discovered through accumulating various research activities that it is difficult to manufacture a steel sheet having surface irregularities as described above, thereby increasing the absorbed energy during crushing deformation, by simply devising hot rolling conditions or annealing conditions alone, and that it can only be manufactured by achieving optimization in a so-called integrated process, including the hot rolling and annealing steps.
[0012] The gist of the present invention is as follows. (1) In mass%, C: less than 0.05 to 0.15%, Si: 0.01 to 2.00%, Mn: 0.10-4.00%, P:0.0200% or less, S: 0.0200% or less, Al: 0.001 to 1.000%, N: 0.0200% or less, Ti: 0 to 0.500%, Co: 0 to 0.500%, Ni: 0 to 0.500%, Mo: 0 to 0.500%, Cr: 0~2.000%, O: 0 to 0.0100%, B: 0~0.0100%, Nb: 0 to 0.500%, V: 0 to 0.500%, Cu: 0 to 0.500%, W: 0~0.1000%, Ta: 0 to 0.1000%, Sn: 0 to 0.0500%, Sb: 0 to 0.0500%, As: 0~0.0500%, Mg: 0 to 0.0500%, Ca: 0 to 0.0500%, Y: 0 to 0.0500%, Zr: 0 to 0.0500%, La: 0 to 0.0500%, and Ce: 0 to 0.0500%, and the balance being Fe and impurities, In terms of area ratio, The sum of ferrite, pearlite and bainite: 0% to 60.0%; and Retained austenite: 0% to 1.0% and the balance has a steel structure consisting of martensite and tempered martensite, There are multiple steps on the plate surface with a height difference of more than 5.0 μm spaced 2.0 mm or less apart. steel plate. (2) In mass%, Ti: 0.001 to 0.500%, Co: 0.001 to 0.500%, Ni: 0.001 to 0.500%, Mo: 0.001 to 0.500%, Cr: 0.001~2.000% O: 0.0001 to 0.0100% B: 0.0001~0.0100%, Nb: 0.001 to 0.500%, V: 0.001 to 0.500%, Cu: 0.001 to 0.500%, W: 0.0001 to 0.1000%, Ta: 0.0001 to 0.1000%, Sn: 0.0001~0.0500%, Sb: 0.0001 to 0.0500%, As: 0.0001 to 0.0500%, Mg: 0.0001 to 0.0500%, Ca: 0.0001 to 0.0500%, Y: 0.0001 to 0.0500%, Zr: 0.0001 to 0.0500%, La: 0.0001 to 0.0500%, and Ce: 0.0001 to 0.0500%, The chemical composition contains one or more of the following: The steel plate according to (1) above. (3) A method for manufacturing a steel sheet, comprising the steps of: hot rolling a steel slab having the chemical composition described in (1) or (2) above to obtain a hot rolled sheet; coiling the hot-rolled sheet; Pickling the hot-rolled sheet; and Annealing the hot-rolled sheet without cold rolling, or annealing the hot-rolled sheet after cold rolling; Including, The hot rolling includes rolling the plate at a reduction ratio of more than 30% and not more than 70% while supplying a lubricant between a rolling roll and the plate in a stand one before a final stand of a finishing mill; The temperature when the hot-rolled sheet is coiled is 700° C. or less, When the cold rolling is performed, the rolling reduction rate in the cold rolling is 0.1 to 20%. Manufacturing method of steel plate. (4) The manufacturing method according to the above-mentioned (3), wherein in the annealing, a coating layer made of zinc, aluminum, magnesium or an alloy thereof is formed on the front and back surfaces of the plate. Effect of the Invention
[0013] According to the present invention, there are provided a steel sheet having excellent energy absorption properties during crushing deformation and a method for producing the same. [Brief description of the drawings]
[0014] [Figure 1] Schematic diagram of the morphology of steps on the steel sheet surface. [Diagram 2] FIG. 2 is a schematic diagram for explaining the difference between the "maximum height roughness Rz" and the "step" referred to in the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, embodiments of the present invention will be described. Note that these descriptions are intended to be merely examples of the embodiments of the present invention, and the present invention is not limited to the following embodiments.
[0016] <Steel plate> The steel sheet according to this embodiment has, in mass%, C: less than 0.05 to 0.15%, Si: 0.01 to 2.00%, Mn: 0.10-4.00%, P:0.0200% or less, S: 0.0200% or less, Al: 0.001 to 1.000%, N: 0.0200% or less, Ti: 0 to 0.500%, Co: 0 to 0.500%, Ni: 0 to 0.500%, Mo: 0 to 0.500%, Cr: 0~2.000%, O: 0 to 0.0100%, B: 0~0.0100%, Nb: 0 to 0.500%, V: 0 to 0.500%, Cu: 0 to 0.500%, W: 0~0.1000%, Ta: 0 to 0.1000%, Sn: 0 to 0.0500%, Sb: 0 to 0.0500%, As: 0~0.0500%, Mg: 0 to 0.0500%, Ca: 0 to 0.0500%, Y: 0 to 0.0500%, Zr: 0 to 0.0500%, La: 0 to 0.0500%, and Ce: 0 to 0.0500%, and the balance being Fe and impurities, In terms of area ratio, The sum of ferrite, pearlite and bainite: 0% to 60.0%; and Retained austenite: 0% to 1.0% and the balance has a steel structure consisting of martensite and tempered martensite, The plate surface is characterized by the presence of multiple steps with a height difference of more than 5.0 μm spaced apart by 2.0 mm or less.
[0017] First, the reason for limiting the chemical composition of the steel sheet according to the present embodiment will be described. Here, "%" for the components means mass%. Furthermore, in this specification, "to" indicating a numerical range is used to mean that the numerical values before and after it are included as the lower limit and upper limit unless otherwise specified.
[0018] (C: less than 0.05-0.15%) C is an element that inexpensively increases tensile strength, and is an extremely important element for suppressing the transformation from austenite to ferrite, bainite, and pearlite in the continuous annealing process and controlling the strength of steel. When the C content is 0.05% or more, such effects are easily obtained. The C content may be 0.07% or more. On the other hand, when C is contained excessively, the area ratio of retained austenite increases, and processing-induced transformation occurs with a small amount of deformation during crushing deformation, which may lead to a decrease in absorbed energy. When the C content is less than 0.15%, such problems are easily avoided. The C content may be 0.13% or less.
[0019] (Si: 0.01 to 2.00%) Silicon acts as a deoxidizer and is an element that suppresses the precipitation of carbides during the cooling process during cold rolling and annealing. When the Si content is 0.01% or more, such an effect is easily obtained. The Si content may be 0.10% or more. On the other hand, excessive Si content increases the strength of the steel and reduces the workability, and further, coarse oxides are dispersed in the surface layer of the hot-rolled sheet, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling and annealing, which may reduce the absorbed energy during crushing deformation. When the Si content is 2.00% or less, such problems are easily avoided. The Si content may be 1.60% or less.
[0020] (Mn: 0.10-4.00%) Mn is a factor that affects the ferrite transformation of steel, and is an element that is effective in increasing strength. When the Mn content is 0.10% or more, such an effect is easily obtained. The Mn content may be 0.60% or more. On the other hand, excessive Mn content increases the strength of the steel and reduces the workability, and further, coarse oxides are dispersed in the surface layer of the hot-rolled sheet, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling and annealing, which may reduce the absorbed energy during crushing deformation. When the Mn content is 4.00% or less, such problems are easily avoided. The Mn content may be 3.00% or less.
[0021] (P:0.0200% or less) P is an element that promotes Mn concentration in unsolidified parts during the solidification process of molten steel, lowers the Mn concentration in negative segregation parts, and promotes an increase in the area ratio of ferrite, and the less P, the better. In addition, excessive P content may increase the strength of the steel and cause brittle fracture of the steel, which may promote a decrease in absorbed energy during crushing deformation. The P content may be 0%, 0.0001% or more, 0.0010% or more, and 0.0200% or less, or 0.0180% or less.
[0022] (S:0.0200% or less) S is an element that generates nonmetallic inclusions such as MnS in steel and reduces the ductility of steel parts, so the less S, the better. In addition, excessive S content can cause cracks to occur starting from the nonmetallic inclusions during crushing deformation, and can also make it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which can reduce the absorbed energy during crushing deformation. The S content may be 0%, 0.0001% or more, 0.0005% or more, 0.0200% or less, or 0.0180% or less.
[0023] (Al: 0.001 to 1.000%) Al is an element that acts as a deoxidizer for steel and stabilizes ferrite, and is added as necessary. When the Al content is 0.001% or more, such an effect is easily obtained. The Al content may be 0.010% or more. On the other hand, when Al is contained excessively, ferrite transformation and bainite transformation during the cooling process in annealing may be excessively promoted, and the strength of the steel sheet may decrease. In addition, when Al is contained excessively, coarse and large amounts of Al oxides are generated on the steel sheet surface during hot rolling, making it difficult to obtain the desired unevenness on the steel sheet surface, which may lead to a decrease in absorbed energy during crushing deformation. When the Al content is 1.000% or less, such problems are easily avoided. The Al content may be 0.800% or less.
[0024] (N:0.0200% or less) N is an element that forms coarse nitrides in the steel sheet and reduces the workability of the steel sheet. N is also an element that causes blowholes during welding. Excessive N content combines with Al and Ti to generate a large amount of AlN or TiN, and these nitrides suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling and annealing, which may lead to a decrease in absorbed energy during crushing deformation. The N content may be 0%, 0.0001% or more, 0.0010% or more, 0.0200% or less, or 0.0160% or less.
[0025] The basic chemical composition of the steel sheet in this embodiment is as described above. Furthermore, the steel sheet in this embodiment may contain at least one of the following optional elements as necessary. These elements do not necessarily have to be contained, so the lower limit is 0%.
[0026] (Ti:0~0.500% or less) Ti is a strengthening element. It contributes to increasing the strength of the steel sheet through precipitation strengthening, fine grain strengthening by suppressing the growth of crystal grains, and dislocation strengthening through suppression of recrystallization. On the other hand, excessive Ti content increases the precipitation of coarse carbides, which suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may lead to a decrease in absorbed energy during crushing deformation. The Ti content may be 0%, 0.001% or more, 0.005% or more, 0.500% or less, or 0.400% or less.
[0027] (Co:0~0.500% or less) Co is an element effective in controlling the morphology of carbides and increasing strength, and is added as necessary to control strength. On the other hand, excessive Co content causes a large number of fine Co carbides to precipitate, which suppresses contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may lead to a decrease in absorbed energy during crushing deformation. The Co content may be 0%, 0.001% or more, and may be 0.500% or less, or 0.400% or less.
[0028] (Ni:0~0.500% or less) Ni is a strengthening element and is effective in improving hardenability. In addition, Ni may be added because it improves the wettability between the steel sheet and the plating and promotes the alloying reaction. On the other hand, excessive Ni content affects the peelability of oxide scale during hot rolling, promotes the generation of scratches on the steel sheet surface, makes it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, and may lead to a decrease in absorbed energy during crushing deformation. The Ni content may be 0%, 0.001% or more, and may be 0.500% or less, or 0.400% or less.
[0029] (Mo: 0 to 0.500% or less) Mo is an element effective in improving the strength of steel sheets. Mo is also an element that has the effect of suppressing ferrite transformation that occurs during heat treatment in continuous annealing equipment or continuous hot-dip galvanizing equipment. On the other hand, if Mo is contained excessively, a large number of fine Mo carbides are precipitated, and these carbides suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may lead to a decrease in absorbed energy during crushing deformation. The Mo content may be 0%, 0.001% or more, and may be 0.500% or less, or 0.400% or less.
[0030] (Cr:0~2.000% or less) Like Mn, Cr is an element that suppresses pearlite transformation and is effective in increasing the strength of steel, and is added as necessary. On the other hand, excessive Cr content promotes the formation of retained austenite, and the presence of excess retained austenite increases the number of fracture initiation points during crushing deformation, which may lead to a decrease in absorbed energy during crushing deformation. The Cr content may be 0%, 0.001% or more, 2.000% or less, or 1.500% or less.
[0031] (O:0~0.0100% or less) Since O forms oxides and deteriorates workability, the content must be suppressed. In particular, oxides often exist as inclusions, and if granular coarse oxides exist on the surface of the steel sheet, it may cause cracks on the surface of the steel sheet and the generation of fine iron powder during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling and annealing, and may cause a decrease in absorbed energy during crushing deformation. The O content may be 0.0100% or less, or may be 0.0080% or less. Note that the O content may be 0%, but controlling the O content to less than 0.0001% may increase the refining time and increase the manufacturing cost. In order to prevent an increase in manufacturing costs, the O content may be 0.0001% or more, or may be 0.0010% or more.
[0032] (B:0~0.0100% or less) B is an element that suppresses the formation of ferrite and pearlite during the cooling process from austenite and promotes the formation of low-temperature transformation structures such as bainite or martensite. In addition, B is an element that is beneficial for increasing the strength of steel and is added as necessary. On the other hand, excessive B content leads to the formation of coarse B oxides in the steel, which suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may lead to a decrease in absorbed energy during crushing deformation. The B content may be 0%, 0.0001% or more, 0.0010% or more, 0.0100% or less, or 0.0080% or less.
[0033] (Nb:0~0.500% or less) Nb is an element effective for controlling the morphology of carbides, and its addition refines the structure, so it is also effective for improving toughness. On the other hand, if Nb is contained excessively, a large number of fine and hard Nb carbides are precipitated, and these carbides suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may lead to a decrease in absorbed energy during crushing deformation. The Nb content may be 0%, 0.001% or more, 0.500% or less, or 0.400% or less.
[0034] (V:0~0.500% or less) V is a strengthening element. It contributes to increasing the strength of the steel sheet through precipitation strengthening, fine grain strengthening by inhibiting the growth of ferrite crystal grains, and dislocation strengthening through inhibiting recrystallization. On the other hand, excessive V content increases the precipitation of carbonitrides, which suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may lead to a decrease in absorbed energy during crushing deformation. The V content may be 0%, 0.001% or more, 0.500% or less, or 0.400% or less.
[0035] (Cu:0~0.500% or less) Cu is an element effective in improving the strength of steel sheets. On the other hand, if Cu is contained excessively, the steel material becomes embrittled during hot rolling, making hot rolling impossible. Furthermore, the Cu layer concentrated on the steel sheet surface suppresses contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may lead to a decrease in absorbed energy during crushing deformation. The Cu content may be 0%, 0.001% or more, 0.500% or less, or 0.400% or less.
[0036] (W:0~0.1000% or less) W is effective in increasing the strength of steel sheets, and precipitates and crystallized materials containing W act as hydrogen trapping sites. On the other hand, excessive W content generates coarse carbides, which suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may lead to a decrease in absorbed energy during crushing deformation. The W content may be 0%, 0.0001% or more, 0.0010% or more, 0.1000% or less, or 0.0800% or less.
[0037] (Ta:0~0.1000% or less) Ta, like Nb, V, and W, is an element effective in controlling the morphology of carbides and increasing strength, and is added as necessary. On the other hand, if Ta is contained excessively, a large number of fine Ta carbides are precipitated, and these carbides suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may lead to a decrease in absorbed energy during crushing deformation. The Ta content may be 0%, 0.0001% or more, 0.0010% or more, 0.1000% or less, or 0.0800% or less.
[0038] (Sn:0~0.0500% or less) Sn is an element contained in steel when scrap is used as a raw material, and the less the better. Excessive Sn content may cause cracks on the steel sheet surface and the generation of fine iron powder during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling and annealing, and may cause a decrease in absorbed energy during crushing deformation. The Sn content may be 0.0500% or less, or 0.0400% or less. The Sn content may be 0%, but controlling the Sn content to less than 0.0001% may increase the refining time and increase the manufacturing cost. In order to prevent an increase in manufacturing costs, the Sn content may be 0.0001% or more, or 0.0010% or more.
[0039] (Sb:0~0.0500% or less) Sb, like Sn, is an element contained when scrap is used as a steel raw material. Sb strongly segregates at grain boundaries, which leads to embrittlement of the grain boundaries and a decrease in ductility, so the less Sb, the better. In addition, excessive Sb content may cause cracks on the steel sheet surface and the generation of fine iron powder during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, and may lead to a decrease in absorbed energy during crushing deformation. The Sb content may be 0.0500% or less, or 0.0400% or less. The Sb content may be 0%, but controlling the Sn content to less than 0.0001% may increase the refining time and increase the manufacturing cost. In order to prevent an increase in manufacturing costs, the Sb content may be 0.0001% or more, or 0.0010% or more.
[0040] (As:0~0.0500% or less) Like Sn and Sb, As is an element that is contained when scrap is used as a steel raw material and strongly segregates at grain boundaries, and the less the better. In addition, excessive As content may cause cracks on the steel sheet surface and the generation of fine iron powder during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, and may cause a decrease in absorbed energy during crushing deformation. The As content may be 0.0500% or less, or 0.0400% or less. The As content may be 0%, but controlling the As content to less than 0.0001% may increase the refining time and increase the manufacturing cost. In order to prevent an increase in manufacturing costs, the As content may be 0.0001% or more, or 0.0010% or more.
[0041] (Mg:0~0.0500% or less) Mg is an element that can control the morphology of sulfides by adding a small amount, and is added as necessary. On the other hand, excessive Mg content forms coarse inclusions, which suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may lead to a decrease in absorbed energy during crushing deformation. The Mg content may be 0%, 0.0001% or more, 0.0010% or more, 0.0500% or less, or 0.0400% or less.
[0042] (Ca:0~0.0500% or less) Ca is useful as a deoxidizing element and is also effective in controlling the morphology of sulfides. On the other hand, excessive Ca content may cause cracks on the steel sheet surface and the generation of fine iron powder during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, and may cause a decrease in absorbed energy during crushing deformation. The Ca content may be 0%, 0.0001% or more, 0.0010% or more, 0.0500% or less, or 0.0400% or less.
[0043] (Y:0~0.0500% or less) Y is an element that can control the morphology of sulfides by adding a small amount, similar to Mg and Ca, and is added as necessary. On the other hand, if Y is contained excessively, coarse Y oxides are generated, which suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may lead to a decrease in absorbed energy during crushing deformation. The Y content may be 0%, 0.0001% or more, 0.0010% or more, 0.0500% or less, or 0.0400% or less.
[0044] (Zr:0~0.0500% or less) Zr is an element that can control the form of sulfides by adding a small amount, similar to Mg, Ca, and Y, and is added as necessary. On the other hand, if Zr is contained excessively, coarse Zr oxides are generated, and the Zr oxides suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may lead to a decrease in absorbed energy during crushing deformation. The Zr content may be 0%, 0.0001% or more, 0.0010% or more, 0.0500% or less, or 0.0400% or less.
[0045] (La:0~0.0500% or less) La is an element that is effective in controlling the morphology of sulfides when added in small amounts, and is added as necessary. On the other hand, if La is contained in excess, La oxides are generated, which suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may lead to a decrease in absorbed energy during crushing deformation. The La content may be 0%, 0.0001% or more, 0.0010% or more, and 0.0500% or less, or 0.0400% or less.
[0046] (Ce:0~0.0500% or less) Ce is an element that can control the morphology of sulfides by adding a small amount, similar to La, and is added as necessary. On the other hand, if Ce is contained excessively, Ce oxides are generated, and the Ce oxides suppress the contact between the steel sheet surface and the roll during hot rolling, making it difficult to obtain the desired unevenness on the surface of the steel sheet after cold rolling annealing, which may lead to a decrease in absorbed energy during crushing deformation. The Ce content may be 0%, 0.0001% or more, 0.0010% or more, and 0.0500% or less, or 0.0400% or less.
[0047] In the steel sheet according to the present embodiment, the balance of the above-mentioned components is Fe and impurities. The impurities are components that are mixed in due to various factors in the manufacturing process, including raw materials such as ores and scraps, when the steel sheet according to the present embodiment is industrially manufactured.
[0048] Next, the features of the steel structure and properties of the steel plate according to this embodiment will be described.
[0049] (Total area ratio of ferrite, pearlite and bainite: 0~60.0%) Although the total area ratio of ferrite, pearlite and bainite is an effective structure for improving the strength-ductility balance of the steel plate, a large content of these elements leads to a decrease in local ductility and reduces the absorbed energy during crushing deformation. In addition, from the viewpoint of efficiently increasing the strength of the steel, it is preferable that the area ratio of ferrite, pearlite and bainite is as small as possible. The total area ratio of ferrite, pearlite and bainite may be 0%, 1.0% or more, 60.0% or less, 55.0% or less, or 50.0% or less. Although the productivity is somewhat reduced, it is possible to make the total area ratio of ferrite, pearlite and bainite 0% by controlling the integrated manufacturing conditions with high precision.
[0050] (Area ratio of retained austenite: 0~1.0%) The area ratio of the retained austenite is an effective structure for improving the strength-ductility balance of the steel plate. On the other hand, if the area ratio of the retained austenite is too large, the proportion of chemically unstable austenite increases, and deformation-induced transformation occurs with a small amount of deformation during crushing deformation, which may lead to a decrease in absorbed energy. The area ratio of the retained austenite may be 0%, 0.1% or more, 1.0% or less, or 0.8% or less.
[0051] (balance: martensite and tempered martensite) Martensite and tempered martensite are extremely effective structures for increasing the strength of steel sheets, and the higher the area ratio, the more preferable. For example, the remainder other than the above structures may be martensite and tempered martensite. The total area ratio of martensite and tempered martensite may be 30.0% or more, 35.0% or more, 40.0% or more, 45.0% or more, 50.0% or more, 100%, or 99.0% or less. Although the productivity decreases, it is possible to make the total area ratio of martensite and tempered martensite 100% by controlling the integrated manufacturing conditions with high precision.
[0052] (Surface unevenness) The interval between steps having a height difference of more than 5.0 μm on the surface of the steel sheet is an important factor that functions as a starting point of bending deformation of the steel sheet when it is subjected to crushing deformation. The shorter the interval, the more preferable. Specifically, it is important that a plurality of steps having a height difference of more than 5.0 μm are present at intervals of 2.0 mm or less on the surface of the steel sheet according to this embodiment. The interval may be 1.8 mm or less, 1.5 mm or less, 1.2 mm or less, 1.0 mm or less, 0.7 mm or less, or 0.4 mm or less. If the interval is less than 0.01 mm, the surface of the steel sheet may have a sawtooth shape. In this regard, the interval may be 0.01 mm or more, or 0.05 mm or more. In addition, in the steel sheet according to this embodiment, it is necessary that a plurality of steps having a height difference of more than 5.0 μm are present dispersedly on the surface of the steel sheet at the above intervals. In particular, when multiple steps having a height difference of 7.0 μm or more or 10.0 μm or more are present at the above intervals and distributed on the steel sheet surface, the steel sheet has even better energy absorption properties during crushing deformation. The upper limit of the height difference of the steps is not particularly limited, and may be, for example, 20.0 μm or less, 15.0 μm or less, or 10.0 μm or less. In the steel sheet according to this embodiment, multiple steps having a height difference of more than 5.0 μm may be present at intervals of 2.0 mm or less over 50 area% or more, 60 area% or more, 70 area% or more, 80 area% or more, or 90 area% or more of the steel sheet surface.
[0053] FIG. 1 shows an example of a "step having a height difference of more than 5.0 μm". FIG. 1 shows the shape of the step when observing the cross section of the steel sheet in the thickness direction. As shown in FIG. 1, the steel sheet surface may have repeated unevenness in the rolling direction, and the height difference of the step specified by each unevenness exceeds 5.0 μm, and the step is included in a range of 2.0 mm or less, that is, the interval between the steps is 2.0 mm or less. In the present invention, at least some of the steps among the multiple steps may have a so-called negative angle portion (undercut portion). In the present invention, the heights of the multiple steps may be different from each other, for example, the heights of each may be irregularly (randomly) different. In addition, the shapes of the multiple steps may be different from each other. In addition, the intervals between the multiple steps do not need to be constant, and may be irregularly (randomly) different. Such a step shape can be formed by a method described later.
[0054] In addition, the "step having a height difference of more than 5.0 μm" in the present application is a concept different from general surface roughness such as maximum height roughness Rz and arithmetic mean roughness Ra. For example, the "maximum height roughness Rz" means the distance between the most convex part and the most concave part of the surface unevenness (maximum difference in height), as shown in FIG. 2(A), and the distribution (spacing) of the surface unevenness cannot be specified from the "maximum height roughness Rz". In addition, the "arithmetic mean roughness Ra" is merely an average value of the surface roughness, and its maximum value is unknown, and the distribution (spacing) of the surface unevenness cannot be specified from the "arithmetic mean roughness Ra". In contrast, the "step having a height difference of more than 5.0 μm" in the present application means that the height difference of "one step" exceeds 5.0 μm, as shown in FIG. 2(B), and the step must exist in a plurality of steps spaced 2.0 mm or less apart.
[0055] (yield strength) In order to reduce the weight of a structure using steel as a material and to improve the strength at which plastic deformation begins, it is preferable that the yield strength of the steel material is high. On the other hand, if the yield strength is too high, the effect of shape change due to elastic deformation after plastic processing, so-called springback, becomes large, and formability may decrease. The yield strength of the steel plate according to this embodiment is not particularly limited, but may be 500 MPa or more, 550 MPa or more, 1100 MPa or less, or 1050 MPa or less.
[0056] (Tensile strength) In order to reduce the weight of a structure using steel as a material and to improve the resistance of the structure to plastic deformation, it is preferable that the steel material has a large work hardening ability and exhibits maximum strength. On the other hand, if the tensile strength is too high, it may be prone to fracture with low energy during plastic deformation, and formability may be reduced. The tensile strength of the steel plate is not particularly limited, but may be 900 MPa or more, 980 MPa or more, 1470 MPa or less, 1410 MPa or less, 1350 MPa or less, or 1310 MPa or less.
[0057] (Total elongation) When manufacturing a structure by cold forming a steel sheet as a raw material, elongation is required to finish the structure into a complex shape. If the total elongation is too low, the raw material may crack during cold forming. On the other hand, the higher the total elongation, the better, but if the total elongation is excessively increased, a large amount of retained austenite is required in the steel structure, which may reduce the absorbed energy during crushing deformation. The total elongation of the steel sheet is not particularly limited, but may be 5% or more, 8% or more, 20% or less, or 18% or less.
[0058] (Hole expandability) When manufacturing a structure by cold forming a steel sheet as a material, hole expandability is necessary as well as elongation in order to finish the structure into a complex shape. If the hole expandability is too small, the material may crack during cold forming. On the other hand, although the higher the hole expandability, the more preferable it is, if the hole expandability is excessively increased, a large amount of retained austenite is required in the steel structure, which may reduce the absorbed energy during crushing deformation. The hole expansion ratio of the steel sheet is not particularly limited, but may be 20% or more, 25% or more, 90% or less, or 80% or less.
[0059] (bendability) When manufacturing a structure by cold forming a steel plate, which is a raw material, bendability is also required to finish it into a complex shape. For example, the VDA bending angle α obtained from a test conforming to the provisions of standard 238-100 of the German Association of the Automotive Industry (Verband der Automobilindustrie: VDA) is an index of bendability. If the VDA bending angle is too small, the material may crack during cold forming. The higher the bendability, the better. The VDA bending angle of the steel plate is not particularly limited, but may be 45° or more, or may be 50° or more. Note that the VDA bending angle presented here is a characteristic value for a plate thickness of 1.4 mm, and a high bending angle value can be obtained even for the same steel plate with a plate thickness of less than 1.4 mm. In addition, when the plate thickness exceeds 1.4 mm, it is preferable to remove one side of the plate by surface grinding, finish the plate thickness to 1.4 mm, and then obtain the bending angle by bending the ground surface on the inside and the non-ground surface on the outside.
[0060] (Thickness) The plate thickness is a factor that affects the rigidity of the steel member after forming, and the greater the plate thickness, the higher the rigidity of the member. If the plate thickness is too small, the rigidity will decrease, and press formability may decrease due to the influence of unavoidable non-ferrous inclusions present inside the steel plate. On the other hand, if the plate thickness is too large, the press forming load will increase, leading to wear of the mold and a decrease in productivity. The plate thickness of the steel plate is not particularly limited, but may be 0.2 mm or more and 6.0 mm or less. The "steel plate" referred to in this application may be a single-layer steel plate. Here, the "single-layer steel plate" means that it is not a so-called multi-layer steel plate, and refers to a steel plate in which the joint interface between the base steel plates is not observed in the plate thickness direction when the cross section of the steel plate is observed. For example, it is a steel plate consisting of one slab. The "plate thickness" of the above steel plate may be the plate thickness as a single-layer steel plate. In addition, the single-layer steel plate may have a surface treatment layer such as a plating layer formed on its surface. In other words, the steel plate referred to in this application may have a single-layer steel plate and a surface treatment layer.
[0061] Next, the methods for observing and measuring the above-specified structure, and the methods for measuring and evaluating the above-specified characteristics will be described.
[0062] (Method for measuring the total area ratio of ferrite, pearlite, and bainite) The structure observation is performed using a scanning electron microscope (SEM). Prior to the observation, the sample for structure observation is wet-polished with emery paper and polished with diamond abrasives with an average particle size of 1 μm, the observation surface is mirror-finished, and the structure is etched with a 3% nitric acid alcohol solution. The magnification of the observation is 3000 times, and 10 random images are taken of a 30 μm x 40 μm field of view at each 1 / 4 thickness position from the surface side of the steel plate. The structure ratio is obtained by the point count method. A total of 100 lattice points are set at intervals of 3 μm vertically and 4 μm horizontally on the obtained structure image, and the structure present under the lattice points is identified, and the structure ratio contained in the steel plate is obtained from the average value of the 10 images. Ferrite is a blocky crystal grain that does not contain iron-based carbides with a major axis of 100 nm or more inside. Bainite is a collection of lath-shaped crystal grains that does not contain iron-based carbides with a long diameter of 20 nm or more, or that contains iron-based carbides with a long diameter of 20 nm or more and the carbides belong to a single variant, i.e., a group of iron-based carbides elongated in the same direction. Here, a group of iron-based carbides elongated in the same direction means that the difference in the elongation direction of the iron-based carbides is within 5°. Bainite grains are counted as bainite surrounded by grain boundaries with an orientation difference of 15° or more. Here, the "grain boundaries with an orientation difference of 15° or more" are obtained using SEM-EBSD in the following procedure. Prior to the SEM-EBSD measurement, the observation surface of the measurement sample is polished to a mirror finish, and further distortion caused by polishing is removed. As in the above SEM observation, a field of view of 30 μm × 40 μm is set as the measurement range at each 1 / 4 position of the thickness from the surface side of the steel plate, and crystal orientation data of BCC iron is obtained by SEM-EBSD. The EBSD measurement is performed using an EBSD detector attached to the SEM, and the measurement interval (STEP) is 0.05 μm. In this case, in the present invention, the software "OIMDataCollectionTM (ver.7)" manufactured by TSL Solutions Co., Ltd. is used as the data acquisition software for the crystal orientation. In the crystal orientation MAP data of BCC iron obtained under these measurement conditions, the boundaries with a crystal orientation difference of 15° or more are identified as crystal grain boundaries, except for the region with a confidence value (CI value) of less than 0.1.Bainite can be said to be a mixed structure of bainitic ferrite, which is made up of a body-centered cubic structure of iron, and iron-based carbide (Fe3C). Bainitic ferrite is distinguished from the above-mentioned ferrite. Pearlite is a structure that contains cementite precipitated in rows, and the area that is photographed with bright contrast in the secondary electron image is considered to be pearlite, and the area ratio is calculated.
[0063] (How to distinguish between martensite and tempered martensite) Martensite and tempered martensite are observed with scanning and transmission electron microscopes, and those containing Fe-based carbides inside are identified as tempered martensite, and those containing almost no carbides are identified as martensite. Fe-based carbides having various crystal structures have been reported, and any Fe-based carbide may be contained. Depending on the heat treatment conditions, multiple types of Fe-based carbides may be present. In this application, the total area ratio A1 of ferrite, pearlite, and bainite is measured by the above method, the area ratio A2 of retained austenite is measured by the method described below, and the remainder obtained by subtracting the total value of the area ratios A1 and A2 from 100% is considered to be the total area ratio of martensite and tempered martensite.
[0064] (Method for measuring area ratio of retained austenite) The area fraction of retained austenite is determined by X-ray measurement as follows. First, the portion from the surface of the steel plate to 1 / 4 of the thickness of the steel plate is removed by mechanical polishing and chemical polishing, and the chemically polished surface is measured using MoKα rays as characteristic X-rays. Then, the area fraction of retained austenite in the center of the plate thickness is calculated using the following formula from the integrated intensity ratio of the diffraction peaks of (200) and (211) of the body-centered cubic lattice (bcc) phase and (200), (220), and (311) of the face-centered cubic lattice (fcc) phase. Sγ=(I200f+I220f+I311f) / (I200b+I211b)×100 (Sγ is the area fraction of retained austenite at the center of the sheet thickness, I200f, I220f, and I311f indicate the intensities of the (200), (220), and (311) diffraction peaks of the fcc phase, respectively, and I200b and I211b indicate the intensities of the (200) and (211) diffraction peaks of the bcc phase, respectively.)
[0065] The sample to be subjected to X-ray diffraction is prepared by reducing the thickness of the steel plate from the surface to a predetermined thickness by mechanical polishing, etc., and then removing distortion by chemical polishing or electrolytic polishing, etc., and adjusting the sample according to the above-mentioned method so that an appropriate surface becomes the measurement surface within the range of 1 / 8 to 3 / 8 of the plate thickness. Naturally, the material anisotropy is further reduced by satisfying the above-mentioned X-ray intensity limit not only in the vicinity of 1 / 4 of the plate thickness but also for as many thicknesses as possible. However, by measuring 1 / 8 to 3 / 8 of the plate surface, the material properties of the entire steel plate can be roughly represented. Therefore, the measurement range is set to 1 / 8 to 3 / 8 of the plate thickness.
[0066] (Method of measuring the distance between surface irregularities (steps with height difference of more than 5.0 μm)) The height difference and distribution interval of the unevenness on the steel sheet surface are measured using a scanning electron microscope (FE-SEM: Field Emission Scanning Electron Microscope). Prior to observation using SEM, a sample for microstructural observation with a length in the rolling direction of more than 20 mm is embedded in resin, and the surface parallel to the rolling direction and perpendicular to the sheet thickness direction (TD surface: Transversal Direction surface) is polished to a mirror finish. The SEM observation magnification is set to 1000 times, and a field of view that includes both the steel sheet and resin within an observation range that is more than 110 μm in the rolling direction and more than 70 μm in the sheet thickness direction is obtained over a rolling length of 20 mm, and a series of photographs that capture the unevenness on the steel sheet surface are obtained. In this continuous photograph, a location where the height difference of the unevenness on the steel sheet surface exceeds 5 μm within a length of 20 μm in the rolling direction is defined as "a step having a height difference of more than 5.0 μm on the steel sheet surface," and the average distance between the tops of the steps within a length of 20 mm in the rolling direction, which is the shooting range of the continuous photograph, is defined as "the distance between steps having a height difference of more than 5.0 μm on the steel sheet surface." Note that in this application, minute unevenness with a height difference of 1.0 μm or less is not considered to be a "step."
[0067] Furthermore, even if the steel plate has been formed or processed into some kind of component, by obtaining a part of the component after forming or processing (e.g., a flat part) and analyzing its surface condition, it is possible to determine whether the component had steps with a height difference of more than 5.0 μm at intervals of 2.0 mm or less when it was in the state of a steel plate before being formed or processed.
[0068] (Methods for measuring yield strength, tensile strength and total elongation) The tensile test for measuring the yield strength, tensile strength and total elongation is performed in accordance with JIS Z 2241, using a JIS No. 5 test piece taken in such a way that the longitudinal direction of the test piece is parallel to the rolling direction perpendicular to the steel strip.
[0069] (Method of measuring hole expandability) The hole expandability is evaluated by punching a circular hole with a diameter of 10 mm under conditions where the clearance is 12.5%, forming it with a 60° conical punch so that the burr is on the die side, and measuring the hole expansion ratio λ (%). Five hole expansion tests are performed for each condition, and the average value is the hole expansion ratio.
[0070] <Steel sheet manufacturing method> The method for producing a steel sheet according to this embodiment is characterized by the consistent management of hot rolling, cold rolling, and annealing using materials with the above-mentioned composition ranges. Specifically, the method for producing a steel sheet according to this embodiment is characterized by including the steps of hot rolling a steel piece (steel slab) having the same chemical composition as that described above for the steel sheet at a predetermined rolling reduction using a lubricant in a rolling mill one step before the final finishing rolling mill, coiling the resulting hot-rolled sheet, pickling it, cold rolling it, and then annealing it. More specifically, the method for producing a steel sheet according to this embodiment is characterized by the steps of: hot rolling the steel slab having the above chemical composition to obtain a hot rolled sheet; coiling the hot-rolled sheet; Pickling the hot-rolled sheet; and The method includes annealing the hot-rolled sheet without cold rolling, or annealing the hot-rolled sheet after cold rolling, The hot rolling includes rolling the plate at a reduction ratio of more than 30% and not more than 70% while supplying a lubricant between a rolling roll and the plate in a stand one before a final stand of a finishing mill; The temperature when the hot-rolled sheet is coiled is 700° C. or less, When the cold rolling is performed, the rolling reduction rate in the cold rolling is 0.1 to 20%. Each step will be described in detail below, focusing on the key points of this embodiment.
[0071] (Reduction rate at the stand before the final stand of the finishing mill) The reduction ratio at the stand immediately preceding the final stand of the finishing rolling mill is a factor that affects the surface condition of the steel sheet. Here, a lubricant (for example, an aqueous solvent mixed with a lubricant) is supplied to the surface of the rolled material (sheet) before rolling at the stand immediately preceding the final stand, and the sheet is rolled with high surface pressure while the lubricant remains on the sheet surface, thereby intermittently providing partial slip and contact between the sheet and the roll surface during rolling, thereby increasing the surface unevenness of the sheet. If the reduction ratio is too small, the surface pressure between the sheet and the roll during rolling is insufficient, and as a result, the desired surface unevenness cannot be formed in the finally obtained steel sheet. Also, if the reduction ratio is too large, the surface pressure generated between the sheet and the roll during rolling becomes excessively high, and the frequency of contact rather than slip between the sheet and the roll increases, making it difficult to provide the finally obtained steel sheet with the desired surface unevenness. From the above viewpoints, in this embodiment, the reduction ratio in the stand immediately preceding the final stand of the finishing mill in hot rolling is more than 30% and not more than 70%, and preferably 35% or more and 60% or less. Note that it is difficult to perform a large reduction in the final stand of the finishing mill in order to correct the shape of the plate. The reduction ratio in the final stand of the finishing mill may be, for example, 20% or less.
[0072] In addition, it is possible to form a step on the surface of the hot-rolled steel sheet after finish rolling by controlling the cumulative reduction rate up to the final stand to be light reduction (for example, cumulative reduction rate of 20% or less) by supplying lubricant at a stand before the final stand. In this regard, the large reduction for increasing the surface unevenness of the sheet may be performed at a stand upstream of the stand immediately preceding the final stand. However, the sheet temperature is high on the upstream side of the finish rolling, and the shape of the sheet surface is easily changed by reduction. In other words, after the large reduction, it is necessary to control the cumulative reduction rate while taking into consideration the influence of temperature. In this regard, it is easier to form a desired step on the surface of the steel sheet by performing a large reduction of 30% or more while supplying lubricant at the downstream side of the finish rolling, particularly at the stand immediately preceding the final stand, and then performing a light reduction at the final stand to adjust the sheet shape.
[0073] Various lubricants can be used. For example, the lubricant may contain ester, mineral oil, polymer, fatty acid, S-based additive, or Ca-based additive. The viscosity of the lubricant is 250 mm. 2 The lubricant may be mixed with water as described above. The amount of lubricant supplied is not particularly limited. For example, the lubricant may be 0.1 g / m2 on the steel sheet surface. 2 or more than 1.0g / m 2 More than 100.0g / m 2 Less than or equal to 50.0 g / m 2 The following lubricants may be applied to the plate. The means for supplying the lubricant is not particularly limited, and the lubricant may be sprayed onto the plate surface, for example.
[0074] (Coil winding temperature) The temperature when the hot-rolled sheet is coiled (the coiling temperature of the hot-rolled coil) is a factor that controls the state of oxide scale formation in the hot-rolled sheet and affects the strength of the hot-rolled sheet. In order to maintain the surface unevenness generated by hot rolling, it is better for the thickness of the scale formed on the surface of the hot-rolled sheet to be thin, and therefore a low coiling temperature is preferable. In addition, when the coiling temperature is extremely reduced, special equipment is required. In addition, if the coiling temperature is too high, as described above, the oxide scale formed on the surface of the hot-rolled sheet becomes significantly thick, so that the convex parts of the unevenness formed on the surface of the hot-rolled sheet by hot rolling are incorporated into the oxide scale, and the scale is removed by the subsequent pickling, making it difficult to form the desired unevenness on the surface of the hot-rolled sheet. From the above viewpoints, the temperature when the hot-rolled sheet is coiled is 700°C or less, and may be 680°C or less, and may be 0°C or more, or may be 20°C or more.
[0075] (Reduction in cold rolling) The reduction ratio in cold rolling is an important factor for controlling the unevenness of the steel sheet surface as well as the shape of the hot rolled sheet. When cold rolling is performed, if the reduction ratio is too small, the shape defect of the hot rolled sheet cannot be corrected and the curvature of the steel strip remains, which may lead to a decrease in manufacturability in the subsequent annealing process and a decrease in absorbed energy during crushing deformation of a part formed into a square tube shape. On the other hand, if the reduction ratio in cold rolling is too large, the convex parts of the unevenness formed on the surface of the hot rolled sheet by rolling are crushed by cold rolling, making it difficult to obtain the desired surface unevenness after the subsequent annealing. From the above viewpoints, when cold rolling is performed, the reduction ratio in the cold rolling is 0.1 to 20%. It is preferably 0.3% or more and 18.0% or less.
[0076] On the other hand, the hot-rolled sheet may be annealed as it is without cold rolling, which also makes it easier to obtain a steel sheet having the desired surface irregularities.
[0077] A preferred embodiment of the method for producing a steel sheet having excellent energy absorbency during crushing deformation will be described in detail below. The following description is an example of a preferred embodiment of the finishing temperature in hot rolling, the heat treatment in annealing, the plating treatment, etc., and does not limit the method for producing a steel sheet according to this embodiment.
[0078] (Hot rolling finishing temperature) The finish rolling temperature of hot rolling is a factor that has an effect on controlling the texture of the prior austenite grain size. From the viewpoint of developing the rolling texture of austenite and causing anisotropy in the steel material properties, the finish rolling temperature is preferably 650°C or higher, and from the viewpoint of suppressing the deviation of the texture due to abnormal grain growth of austenite, the finish rolling temperature is desirably, for example, 940°C or lower.
[0079] (Annealing atmosphere) In order to prevent the diffusion of easily oxidizable elements to the steel sheet surface and promote internal oxidation, it is important to control the oxygen potential in the heating zone during annealing. Specifically, annealing is preferably performed in an atmosphere containing 0.1 to 30 volume % hydrogen and H2O with a dew point of -40 to 20°C, with the remainder being nitrogen and impurities. More preferably, the atmosphere contains 0.5 to 20 volume % hydrogen and H2O with a dew point of -30 to 15°C, and even more preferably, the atmosphere contains 1 to 10 volume % hydrogen and H2O with a dew point of -20 to 10°C.
[0080] (Annealing temperature) If the maximum heating temperature during annealing is too low, it may take too long for the carbides formed during hot rolling to redissolve, and the carbides or a part of them may remain, or martensite may not be obtained sufficiently after cooling, making it difficult to ensure the strength of the steel sheet. On the other hand, excessive high-temperature heating not only increases costs, but also induces problems such as poor sheet shape during high-temperature sheet passing and reduced roll life. From the above viewpoints, the maximum heating temperature during annealing (annealing holding temperature) is preferably 750°C or higher and 900°C or lower.
[0081] (Annealing holding time) During annealing, it is preferable to hold the above heating temperature for 5 seconds or more. If the holding time is too short, the austenite transformation of the base steel sheet may not proceed sufficiently, resulting in a significant decrease in strength. In addition, the recrystallization of the ferrite structure may be insufficient, resulting in large variations in hardness. From these viewpoints, the holding time is more preferably 10 seconds or more. More preferably, it is 20 seconds or more.
[0082] (Cooling rate after annealing) In the cooling after the annealing, it is preferable to cool from 750°C to 550°C at an average cooling rate of 100°C / s or less. The lower limit of the average cooling rate is not particularly limited, but may be, for example, 2.5°C / s. The reason for setting the lower limit of the average cooling rate to 2.5°C / s is to suppress the occurrence of ferrite transformation in the base steel sheet and the softening of the base steel sheet. If the average cooling rate is too slow, the strength is likely to decrease. More preferably, it is 5°C / s or more, more preferably 10°C / s or more, and even more preferably 20°C / s or more. Since ferrite transformation is significantly unlikely to occur at 750°C or more, the cooling rate is not limited. Furthermore, since a low-temperature transformation structure is obtained at a temperature of 550°C or less, the cooling rate is not limited. If the cooling rate is too fast, a low-temperature transformation structure is also generated in the surface layer of the steel sheet, which causes variations in hardness. In this respect, the average cooling rate is preferably 100°C / s or less, more preferably 50°C / s or less, and even more preferably 20°C / s or less.
[0083] (Cooling stop temperature after annealing and reheating) After the above cooling, the steel may be further cooled to a temperature of 25°C to 550°C, and then reheated to a temperature range of 350°C to 550°C and retained there if the cooling stop temperature is lower than the plating bath temperature. When cooling is performed within the above temperature range, martensite is generated from untransformed austenite during cooling. By subsequently reheating, the martensite is tempered, carbide precipitation occurs in the hard phase, and dislocation recovery and rearrangement occurs, improving hydrogen embrittlement resistance. The lower limit of the cooling stop temperature is set at 25°C because excessive cooling not only requires significant capital investment, but also saturates its effect.
[0084] (residence temperature) Furthermore, after reheating and before immersion in the plating bath, the steel sheet may be allowed to stay in a temperature range of 350 to 550°C. Staying in this temperature range not only contributes to tempering the martensite, but also eliminates temperature unevenness in the width direction of the sheet, improving the appearance after plating. If the cooling stop temperature is 350 to 550°C, the steel sheet may be allowed to stay without reheating.
[0085] (Residence time) The retention time is preferably 30 seconds or more and 300 seconds or less in order to obtain the desired effect.
[0086] (Tempering) In a series of annealing steps, the cold-rolled sheet or the steel sheet plated on the cold-rolled sheet may be reheated after cooling to room temperature or during cooling to room temperature (but below Ms), and may be held at a temperature range of 150°C to 400°C for 2 seconds or more. According to this step, the martensite formed during cooling after reheating is tempered to form tempered martensite, thereby improving hydrogen embrittlement resistance. When the tempering step is performed, if the holding temperature is too low or the holding time is too short, the martensite is not sufficiently tempered, and there is almost no change in the microstructure and mechanical properties. On the other hand, if the holding temperature is too high, the dislocation density in the tempered martensite decreases, leading to a decrease in tensile strength. Therefore, when tempering is performed, it is preferable to hold at a temperature range of 150°C to 400°C for 2 seconds or more. Tempering may be performed in a continuous annealing facility, or may be performed offline after continuous annealing in a separate facility. In this case, the tempering time varies depending on the tempering temperature. That is, the lower the temperature, the longer the time, and the higher the temperature, the shorter the time.
[0087] (Plating) The steel sheet may be subjected to hot-dip galvanization by heating or cooling to (galvanization bath temperature -40)°C to (galvanization bath temperature +50)°C, as necessary. A hot-dip galvanized layer is formed on the surface of the steel sheet by the hot-dip galvanization step. In this case, the corrosion resistance of the cold-rolled steel sheet is improved, which is preferable. For example, in the manufacturing method according to the present embodiment, a coating layer made of zinc, aluminum, magnesium or an alloy thereof may be formed on the front and back surfaces of the sheet during annealing. Alternatively, the coating layer may be formed on the front and back surfaces of the sheet after annealing.
[0088] (Steel sheet temperature after immersion in plating bath) When alloying treatment is performed on the hot-dip galvanized layer, the steel sheet on which the hot-dip galvanized layer is formed is heated to a temperature range of 450 to 550°C. If the alloying temperature is too low, the alloying may not proceed sufficiently. On the other hand, if the alloying temperature is too high, the alloying may proceed too much, and the Fe concentration in the coating layer may exceed 15% due to the formation of Γ phase, which may deteriorate the corrosion resistance. The alloying temperature is more preferably 470°C or higher, and more preferably 540°C or lower. The alloying temperature needs to be changed depending on the component composition of the steel sheet and the degree of formation of the internal oxide layer, so it may be set while checking the Fe concentration in the coating layer.
[0089] (Plating bath composition) The composition of the plating bath is preferably Zn-based, with an effective Al content (the total Al content minus the total Fe content in the plating bath) of 0.050 to 0.250 mass%. If the effective Al content in the plating bath is too small, Fe may penetrate excessively into the plating layer, resulting in a decrease in plating adhesion. On the other hand, if the effective Al content in the plating bath is too large, Al-based oxides that inhibit the movement of Fe and Zn atoms may be formed at the boundary between the steel sheet and the plating layer, resulting in a decrease in plating adhesion. The effective Al content in the plating bath is more preferably 0.065 mass% or more, and more preferably 0.180 mass% or less.
[0090] (Steel sheet temperature when immersed in plating bath) The temperature of the steel sheet when immersed in the hot-dip galvanizing bath is preferably in the range from a temperature 40°C lower than the hot-dip galvanizing bath temperature (hot-dip galvanizing bath temperature -40°C) to a temperature 50°C higher than the hot-dip galvanizing bath temperature (hot-dip galvanizing bath temperature +50°C). If this temperature is lower than the hot-dip galvanizing bath temperature -40°C, heat removal during immersion in the galvanizing bath is large, and some of the molten zinc may solidify, deteriorating the appearance of the coating. If the temperature of the sheet before immersion is lower than the hot-dip galvanizing bath temperature -40°C, it is acceptable to further heat the sheet before immersion in the galvanizing bath by any method, and control the sheet temperature to the hot-dip galvanizing bath temperature -40°C or higher before immersing it in the galvanizing bath. In addition, if the temperature of the steel sheet when immersed in the galvanizing bath exceeds the hot-dip galvanizing bath temperature +50°C, operational problems due to the rise in the galvanizing bath temperature may be induced.
[0091] (Pre-processing) In order to further improve the coating adhesion, the base steel sheet may be coated with a coating of one or more of Ni, Cu, Co and Fe before annealing in the continuous hot-dip galvanizing line.
[0092] (Post-processing) For the purpose of improving paintability and weldability, the surface of the hot-dip galvanized steel sheet and the alloyed hot-dip galvanized steel sheet may be provided with an upper layer of plating or with various other treatments, such as chromate treatment, phosphate treatment, lubricity improvement treatment, weldability improvement treatment, etc.
[0093] (Skin pass rolling ratio) Furthermore, skin pass rolling may be performed for the purpose of correcting the steel sheet shape and improving ductility by introducing mobile dislocations. The reduction ratio of the skin pass rolling after heat treatment is preferably in the range of 0.1 to 2.0%. If it is less than 0.1%, the effect is small and control is difficult, so this is the lower limit. If it exceeds 2.0%, the productivity drops significantly, so this is the upper limit. The skin pass may be performed inline or offline. In addition, the skin pass may be performed at the desired reduction ratio at one time, or may be performed in several steps. In addition, since the strength of the steel sheet after annealing is higher than that of the hot-rolled sheet, the change in the surface unevenness when rolling is performed at the same reduction ratio is not the same, but in order to maintain the unevenness formed by the hot-rolled sheet, the sum of the cold rolling ratio and the skin pass rolling ratio is preferably 20% or less.
[0094] According to the above manufacturing method, the steel sheet according to the above embodiment can be obtained. EXAMPLES
[0095] An embodiment of the present invention will be described below. The present invention is not limited to this example of conditions. The present invention can adopt various conditions as long as it does not deviate from the gist of the invention and achieves its object.
[0096] (Example 1) Steels having various chemical compositions were melted to produce steel billets. These billets were inserted into a furnace heated to 1220°C, and were subjected to a homogenization treatment of holding for 60 minutes, after which they were taken out into the air and hot rolled to obtain steel plates with a thickness of 1.8 mm. In the hot rolling, the reduction rate in the stand immediately preceding the final stand of the finishing mill was 35%, and lubricant was supplied between the roll and the plate in the stand immediately preceding the final stand. The finishing rolling was completed at a temperature of 910°C, and the plate was cooled to 550°C and wound up. Subsequently, the oxide scale of this hot-rolled steel plate was removed by pickling, and cold rolling was performed at a reduction rate of 12.0%, to finish the plate to a thickness of 1.4 mm. Furthermore, this cold-rolled steel plate was annealed, specifically, the temperature was raised to 860°C, and the holding time in that temperature range was 130 seconds. Next, the cold-rolled steel plate after annealing was cooled and held at 280°C, and then skin pass rolling was performed. The chemical compositions of samples taken from each of the obtained steel sheets were analyzed and are shown in Tables 1-1 to 1-4. The balance other than the components shown in Tables 1-1 to 1-4 is Fe and impurities. Tables 2-1 and 2-2 show the evaluation results of the properties of the steel sheets that were subjected to the above-mentioned thermomechanical treatment.
[0097] In addition, in Tables 2-1 and 2-2, the measurement methods for "area ratio of the structure of the cold-rolled annealed sheet", "tensile properties (tensile strength, total elongation, hole expandability)", and "spacing of steps having a height difference of more than 5.0 μm on the sheet surface" are as described above.
[0098] The "absorbed energy during axial crushing" was evaluated by an axial crushing test on a hat-shaped component (50 mm square, 300 mm long, with a back plate of the same material as the component joined with spot welding intervals of 30 mm). First, the steel plate obtained as described above was bent to produce a molded product having the above-mentioned specified open cross-sectional shape. The end of the molded product was fixed, and a 900 kg weight was accelerated and dropped from a height of 2 m on the side opposite the fixed end, colliding with the impact end of the molded product in the axial direction at a speed of 22 km / h. The impact absorbed energy up to 100 mm crushing was calculated from the load-displacement curve during the axial crushing test. The evaluation criteria for absorbed energy are as follows. If the energy absorption is at or above the OK (△) mark, it can be said to be suitable for automotive applications. OK (pass): Absorbed energy is over 5.5 kJ OK (△): Absorbed energy is over 4.5 kJ and 5.5 kJ or less NG (Fail): Absorbed energy is 4.5 kJ or less
[0099] [Table 1-1]
[0100] [Table 1-2]
[0101] [Table 1-3]
[0102] [Table 1-4]
[0103] [Table 2-1]
[0104] [Table 2-2]
[0105] The results shown in Tables 2-1 and 2-2 reveal the following:
[0106] In AN-1, the carbon content in the steel was too low, which promoted the transformation from austenite to ferrite, bainite, and pearlite during annealing, and it is believed that the tempered martensite and martensite were insufficient, resulting in a decrease in the strength of the steel. As a result, the absorbed energy during axial crushing deformation of the final steel plate was reduced.
[0107] In AO-1, the carbon content in the steel was too high, which is thought to have increased the area ratio of retained austenite and caused deformation-induced transformation to occur with a small amount of deformation during crushing. As a result, the absorbed energy during axial crushing of the final steel plate was reduced.
[0108] AP-1 had too much Si in the steel, which increased the strength of the steel but reduced its workability, and furthermore, it became easier for coarse oxides to disperse in the surface layer of the hot-rolled sheet, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the absorbed energy during axial crushing deformation decreased.
[0109] It is believed that AQ-1 had an excessively high Mn content, which increased the strength of the steel but reduced its workability, and furthermore, coarse oxides were easily dispersed in the surface layer of the hot-rolled sheet, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the absorbed energy during axial crushing deformation decreased.
[0110] The P content in AR-1 steel was too high, which is thought to have led to brittle fracture of the steel while increasing the steel strength. As a result, the absorbed energy during axial crushing deformation of the final steel plate was reduced.
[0111] AS-1 steel contained too much S, so that cracks were likely to occur starting from nonmetallic inclusions during hot rolling, and the steel cracked and peeled off during hot rolling, and the steel sheet surface was polished by the finely pulverized iron powder during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. It is also believed that cracks were likely to occur starting from nonmetallic inclusions during crushing deformation. As a result, the desired unevenness could not be formed on the surface of the finally obtained steel sheet, and the absorbed energy during axial crushing deformation was reduced.
[0112] In AT-1, the Al content in the steel was too high, which accelerated ferrite transformation and bainite transformation during the cooling process of annealing, reducing the steel strength, and also caused the steel sheet surface to be polished during hot rolling by a large amount of coarse Al oxides formed on the steel surface during hot rolling, making it difficult to generate appropriate deformation during hot rolling and to obtain the desired unevenness. As a result, the desired unevenness could not be formed on the surface of the finally obtained steel sheet, and the absorbed energy during axial crushing deformation decreased.
[0113] It is believed that AU-1 had too much N in the steel, which caused excessive nitrides to form in the steel, and the nitrides suppressed contact between the sheet surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the absorbed energy during axial crushing deformation decreased.
[0114] It is believed that AV-1 had too much Ti in the steel, which caused excessive formation of coarse carbides in the steel, which in turn suppressed contact between the plate surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel plate, and the absorbed energy during axial crushing deformation decreased.
[0115] In AW-1, the Co content in the steel was too high, which resulted in the excessive formation of Co carbides in the steel, which suppressed the contact between the sheet surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the absorbed energy during axial crushing deformation decreased.
[0116] The Ni content in AX-1 steel was too high, which affected the peeling of oxide scale during hot rolling and promoted the generation of scratches on the plate surface. As a result, the desired unevenness could not be formed on the surface of the final steel plate, and the absorbed energy during axial crushing deformation decreased.
[0117] It is believed that the Mo content in AY-1 was too high, which resulted in the excessive formation of Mo carbides in the steel, which in turn suppressed contact between the sheet surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the absorbed energy during axial crushing deformation decreased.
[0118] In AZ-1, the Cr content in the steel was too high, which promoted the formation of retained austenite, and it is believed that the presence of excess retained austenite increased the number of fracture initiation points during axial crushing deformation. As a result, the absorbed energy during axial crushing deformation decreased.
[0119] It is believed that the O content in BA-1 steel was too high, which caused coarse granular oxides to form on the steel sheet surface, which led to cracks on the steel sheet surface and the formation of fine iron powder during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the absorbed energy during axial crushing deformation decreased.
[0120] It is believed that the B content in BB-1 was too high, which caused B oxides to form in the steel, which in turn suppressed contact between the sheet surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the absorbed energy during axial crushing deformation decreased.
[0121] In BC-1, the Nb content in the steel was too high, which resulted in the formation of a large amount of Nb carbides in the steel, which suppressed the contact between the plate surface and the roll during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel plate, and the absorbed energy during axial crushing deformation decreased.
[0122] It is believed that the V content in BD-1 was too high, which caused a large amount of carbonitrides to form in the steel, which in turn suppressed contact between the sheet surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the absorbed energy during axial crushing deformation decreased.
[0123] It is believed that the Cu content in BE-1 was too high, causing Cu to concentrate on the plate surface, which in turn suppressed contact between the plate surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel plate, and the absorbed energy during axial crushing deformation decreased.
[0124] It is believed that the W content in BF-1 was too high, which caused carbides to form in the steel, which in turn suppressed contact between the plate surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel plate, and the absorbed energy during axial crushing deformation decreased.
[0125] It is believed that the Ta content in BG-1 was too high, which caused carbides to form in the steel, which in turn suppressed contact between the sheet surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the absorbed energy during axial crushing deformation decreased.
[0126] It is believed that the Sn content in BH-1 steel was too high, which caused cracks on the steel sheet surface and the generation of fine iron powder during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the absorbed energy during axial crushing deformation decreased.
[0127] It is believed that the Sb content in BI-1 was too high, which caused cracks on the steel sheet surface and the generation of fine iron powder during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the absorbed energy during axial crushing deformation decreased.
[0128] It is believed that the As content in BJ-1 was too high, which caused cracks on the steel sheet surface and the generation of fine iron powder during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the absorbed energy during axial crushing deformation decreased.
[0129] It is believed that the Mg content in the steel of BK-1 was too high, which caused coarse inclusions to form in the steel, which in turn suppressed contact between the sheet surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the absorbed energy during axial crushing deformation decreased.
[0130] It is believed that the excessive Ca content in BL-1 caused cracks on the steel sheet surface and the generation of fine iron powder during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the absorbed energy during axial crushing deformation decreased.
[0131] It is believed that the Y content in BM-1 was too high, which caused Y oxides to form in the steel, which suppressed contact between the sheet surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the absorbed energy during axial crushing deformation decreased.
[0132] It is believed that the Zr content in BN-1 was too high, which caused Zr oxides to form in the steel, which suppressed contact between the sheet surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the absorbed energy during axial crushing deformation decreased.
[0133] It is believed that the La content in BO-1 was too high, which caused La oxides to form in the steel, which suppressed contact between the sheet surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the absorbed energy during axial crushing deformation decreased.
[0134] It is believed that the Ce content in BP-1 was too high, which caused Ce oxides to form in the steel, which in turn suppressed contact between the sheet surface and the rolls during hot rolling, making it difficult to obtain the desired unevenness during hot rolling. As a result, the desired unevenness could not be formed on the surface of the final steel sheet, and the absorbed energy during axial crushing deformation decreased.
[0135] For A-1 to AM-1, in which the content of each element is within the specified range, the desired structure was obtained in the final steel plate, and the desired unevenness was formed on the steel plate surface, resulting in excellent energy absorption during axial crushing deformation.
[0136] (Example 2) Furthermore, in order to investigate the influence of manufacturing conditions, the steel types A to AM, which were found to have excellent properties in Example 1, were subjected to thermomechanical processing under the manufacturing conditions shown in Table 3 to prepare cold-rolled steel sheets having a thickness of 1.4 mm, and the properties of the steel sheets after cold-rolling annealing were evaluated. Here, the plated steel sheets were immersed in a hot-dip galvanizing bath and then held at the temperatures shown in Tables 3-1 to 3-4 to prepare alloyed hot-dip galvanized steel sheets in which an alloy plating layer of iron and zinc was provided on the surface of the steel sheets. In addition, during the cold-rolled sheet annealing, the steel sheets were held at the respective residence temperatures, and then were subjected to a tempering treatment in which the steel sheets, which had been cooled once to 150°C, were reheated and held for 2 seconds or more before being cooled to room temperature. The obtained results are shown in Tables 3-1 to 3-4. The method of evaluating the properties was the same as in Example 1.
[0137] [Table 3-1]
[0138] [Table 3-2]
[0139] [Table 3-3]
[0140] [Table 3-4]
[0141] The results shown in Tables 3-1 to 3-4 reveal the following:
[0142] In A-2 and AI-2, the reduction ratio in cold rolling was too large, so it is believed that the convex parts of the unevenness formed on the surface of the plate by hot rolling were crushed by cold rolling. As a result, the desired unevenness could not be formed on the surface of the finally obtained steel plate, and the absorbed energy during axial crushing deformation was reduced.
[0143] In the hot rolling of G-2, lubricant was not supplied to the stand before the final stand of the finishing mill, which is thought to have made it difficult for slippage to occur between the plate and the roll. As a result, the desired unevenness could not be formed on the surface of the final steel plate, and the absorbed energy during axial crushing deformation decreased.
[0144] In the case of S-2 and AB-3, the reduction ratio in the stand before the final stand of the finishing mill was too large during hot rolling, which caused the surface pressure between the plate and the rolls to become excessively high during rolling, and it is believed that this caused the plate and the rolls to contact each other more frequently than to slip. As a result, the desired unevenness could not be formed on the surface of the final steel plate, and the absorbed energy during axial crushing deformation decreased.
[0145] In AH-2 and O-3, the temperature during coiling of the hot-rolled sheet was too high, so that the oxide scale formed on the surface of the hot-rolled sheet became extremely thick, and the convex parts of the unevenness formed on the surface of the hot-rolled sheet by hot rolling were absorbed into the oxide scale, and it is believed that the convex parts were lost when the scale was removed by the subsequent pickling. As a result, the desired unevenness could not be formed on the surface of the finally obtained steel sheet, and the absorbed energy during axial crushing deformation decreased.
[0146] In the case of N-3 and T-3, the reduction ratio in the stand before the final stand of the finishing mill was too small in hot rolling, which is believed to have caused insufficient surface pressure between the plate and the roll during hot rolling, making it difficult to form irregularities. As a result, the desired irregularities could not be formed on the surface of the final steel plate, and the absorbed energy during axial crushing deformation decreased.
[0147] From the results of Examples 1 and 2 above, it was found that a steel plate satisfying the following requirements (I) to (III) has excellent energy absorption properties during axial crush deformation. (I) In mass%, C: 0.05-0.15%, Si: 0.01-2.00%, Mn: 0.10-4.00%, P: 0.0200% or less, S: 0.0200% or less, Al: 0.001-1.000%, N: 0.0200% or less, Ti: 0-0.500%, Co: 0-0.500%, Ni: 0-0.500%, Mo: 0-0.500%, Cr: 0-2.000%, O: 0-0.0100%, B: 0-0.0100%, Nb: 0-0.500%, The chemical composition is V: 0-0.500%, Cu: 0-0.500%, W: 0-0.1000%, Ta: 0-0.1000%, Sn: 0-0.0500%, Sb: 0-0.0500%, As: 0-0.0500%, Mg: 0-0.0500%, Ca: 0-0.0500%, Y: 0-0.0500%, Zr: 0-0.0500%, La: 0-0.0500%, and Ce: 0-0.0500%, with the balance being Fe and impurities. (II) The steel has a steel structure containing, in terms of area ratio, the total of ferrite, pearlite and bainite: 0% or more and 60.0% or less, and retained austenite: 0% or more and 1.0% or less, with the remainder being martensite and tempered martensite. (III) There are multiple steps on the plate surface with a height difference of more than 5.0 μm spaced apart by 2.0 mm or less.
[0148] It has also been found that a steel sheet satisfying the above requirements (I) to (III) can be manufactured by an integrated manufacturing method characterized by increasing the surface roughness of a hot-rolled sheet by adjusting hot-rolling conditions, and then passing through an annealing process without completely smoothing out the roughness. Specifically, it can be said that the steel sheet can be manufactured by the following manufacturing method. hot rolling the steel slab having the chemical composition of (I) to obtain a hot rolled sheet; coiling the hot-rolled sheet; Pickling the hot-rolled sheet; and Annealing the hot-rolled sheet without cold rolling, or annealing the hot-rolled sheet after cold rolling; Including, The hot rolling includes rolling the plate at a reduction ratio of more than 30% and not more than 70% while supplying a lubricant between a rolling roll and the plate in a stand one before a final stand of a finishing mill; The temperature when the hot-rolled sheet is coiled is 700° C. or less, When the cold rolling is performed, the rolling reduction rate in the cold rolling is 0.1 to 20%. Manufacturing method of steel plate.
Claims
1. In mass percent, C: 0.05 to less than 0.15%; Si: 0.01 to 2.00%, Mn: 0.10-4.00%, P: 0.0200% or less, S: 0.0200% or less, Al: 0.001-1.000%, N: 0.0200% or less, Ti: 0 to 0.500%, Co: 0 to 0.500%, Ni: 0 to 0.500%, Mo: 0-0.500%, Cr: 0-2.000%, O: 0 to 0.0100%, B: 0 to 0.0100%, Nb: 0 to 0.500%, V: 0 to 0.500%, Cu: 0-0.500%, W: 0-0.1000%, Ta: 0-0.1000%, Sn: 0-0.0500%, Sb: 0 to 0.0500%, As: 0 to 0.0500%, Mg: 0 to 0.0500%, Ca: 0-0.0500%, Y: 0 to 0.0500%, Zr: 0 to 0.0500%, La: 0 to 0.0500%, and Ce: 0 to 0.0500%, and the balance being Fe and impurities, In terms of area ratio, The sum of ferrite, pearlite and bainite: 0% or more and 60.0% or less, and Retained austenite: 0% or more and 1.0% or less, Martensite: 0.2% or more, and the balance being tempered martensite (excluding a structure in which the area ratio of martensite is 100%), There are a plurality of steps having a height difference of more than 5.0 μm and not more than 20.0 μm on the plate surface at intervals of 2.0 mm or less. Steel plates (excluding hot-rolled steel plates).
2. In mass percent, Ti: 0.001 to 0.500%, Co: 0.001 to 0.500%, Ni: 0.001 to 0.500%, Mo: 0.001-0.500%, Cr:0.001~2.000% O: 0.0001-0.0100% B: 0.0001 to 0.0100%, Nb: 0.001-0.500%, V: 0.001-0.500%, Cu: 0.001 to 0.500%, W: 0.0001-0.1000%, Ta: 0.0001 to 0.1000%, Sn: 0.0001 to 0.0500%, Sb: 0.0001 to 0.0500%, As: 0.0001 to 0.0500%, Mg: 0.0001-0.0500%, Ca: 0.0001-0.0500%, Y: 0.0001-0.0500%, Zr: 0.0001 to 0.0500%, La: 0.0001 to 0.0500%, and Ce: 0.0001 to 0.0500%, The chemical composition contains one or more of the following: The steel sheet according to claim 1.
3. A method for manufacturing a steel sheet according to claim 1 or 2, hot rolling a steel slab having the chemical composition according to claim 1 or 2 to obtain a hot rolled sheet; coiling the hot-rolled sheet; Pickling the hot-rolled sheet; and Annealing the hot-rolled sheet without cold rolling, or annealing the hot-rolled sheet after cold rolling; Including, The hot rolling includes rolling the plate at a reduction ratio of more than 30% and not more than 70% while supplying a lubricant between a rolling roll and the plate in a stand one before a final stand of a finishing mill, The temperature when the hot-rolled sheet is coiled is 700° C. or less, When the cold rolling is performed, the reduction ratio in the cold rolling is 0.1 to 20%. Manufacturing method of steel plate.
4. In the annealing, a coating layer made of zinc, aluminum, magnesium or an alloy thereof is formed on the front and back surfaces of the plate. The method according to claim 3.
Citation Information
Patent Citations
Steel sheet having excellent mold galling resistance
JP1990037901A
Alloyed hot-dip galvanized steel sheet having excellent formability and brightness after painting
JP1990274856A
Steel sheet for working having excellent painting brightness and production thereof
JP1992253503A
Steel sheet for painting having excellent press formability
JP1992333310A
Steel plate excellent in distinctness of coating and scratch resistance
JP1993237505A